Bezoar gastrointestinal disease in children (literature review and interpretation of clinical observation) (Perioperaciina Medicina, 2019)
The article presents data on the causes of the formation of various types of bezoars in children, traces the causes of their complicated course in the form of bezoar disease. Modern issues of diagnostics, methods of treatment and formation of foreign bodies of the digestive tract in children are covered in the article. A clinical case of a giant trichobezoar of the stomach and duodenum in a 14-year-old girl is presented and analyzed. in a histological examination of the gastric wall.
Keywords: bezoar disease; children; trichobezoir; stomach